Differentiation of primary central nervous system lymphoma from high‐grade glioma and brain metastases using susceptibility‐weighted imaging. Issue 6 (10th October 2014) - Ding, Yaling; Xing, Zhen; Liu, Biying; Lin, Xinjian; Cao, Dairong
Abstract Background and Purpose Conventional MRI is often difficult to distinguish between primary central nervous system lymphomas (PCNSLs), high‐grade gliomas and brain metastases due to the similarity of their appearance. The aim of this study was to investigate whether the susceptibility‐weighted imaging (SWI) has higher sensitivity than conventional MRI in detecting hemorrhage between PCNSLs, high‐grade gliomas and brain metastases, and can be used to differentiate the diagnosis between these tumors. Methods The number of lesions with hemorrhage was quantified by both the conventional MR imaging and SWI. The number of micro‐hemorrhage and vessels within lesions were counted on SWI. Results The detection rate of hemorrhage on SWI was significantly higher than that on the conventional MR imaging. The intralesional hemorrhagic burden and the number of the vessels within lesions detected by SWI were significantly higher in high‐grade gliomas and brain metastases than those in PCNSLs. There was no significant difference in these two parameters between high‐grade gliomas and brain metastases. The best predictor to differentiate PCNSLs from high‐grade gliomas and brain metastases was intralesional vessel number that yielded the best ROC characteristics and highest classification accuracy. Conclusions SWI is useful in differentiating of PCNSLs from high‐grade gliomas and brain metastases.